Functional carbon dots from a mild oxidation of coal liquefaction residue. (15th August 2022) - Qin, Fuwei; Li, Qiqi; Tang, Tingting; Zhu, Jiayao; Gan, Xuemeng; Chen, Yaoyao; Li, Yizhao; Zhang, Su; Huang, Xueli; Jia, Dianzeng
Graphical abstract: Functional carbon dots with conjugated core and enriched oxygen-bearing functional groups are prepared in large-scale through mild oxidation of the solid-waste coal liquefaction residue, promoting the efficient and high-value-added utilization of coal resource. Highlights: Coal liquefaction residue is mildly oxidized to prepare functional carbon dots. Carbon dots ( ca. 6.8 nm) show conjugated core and enriched functional groups. The derived microporous carbon and carbon nanofiber show improved performance. Abstract: Effective utilization of the solid-waste coal liquefaction residue (CLR) is important for the development of direct coal liquefaction technology, but remains big challenge due to the high ash of about 30 wt% in CLR. Herein, we propose a mild oxidation method to prepare functional carbon dots (CDs) using CLR as the carbon precursor and piranha solution (H2 O2 /H2 SO4 ) as the oxidant. Through catalytic hydrogenation, the highly conjugated structure of coal converts to weakly linked structure by aliphatic chains in CLR, leading to an improved oxidation reactivity. The highly reactive aliphatic chains are oxidized and cut during oxidation, leading to the formation of CDs with enriched oxygen-bearing functional groups at the edge sites and simultaneous removal of ash. To present the special properties of CDs, we prepare a microporous carbon with high-surface area and compaction density (1345 m 2 g −1 and 0.86 g cm −3 ) through homogeneous activation of CDs, performing both high gravimetric and volumetric capacitance for supercapacitors. CDs are also used as the functional reinforcing phase for activated carbon nanofibers, enabling high surface area, improved mechanical property, good conductivity, and extremely high rate performance for supercapacitors. Our work provides a new avenue for high efficient and high value-added utilization of CLR.